KEMAMPUAN KOMUNIKASI MATEMATIS SISWA PADA MATERI RELASI DAN FUNGSI DI PONDOK PESANTREN ANSHOR AL SUNNAH - Helmi Yanti; Zaenuri Zaenuri; Walid Walid (Jurnal Kajian Pembelajaran Matematika, 2021)
Research purposes for describing student ability communication. Research population is purposive grade VIII Anshor Al Sunnah boarding school in academic year 2020/2021. Research sample is student grade VIII A at boarding school Anshor Al Sunnah. Research aminstrument is mathematics communication ability. The data analysis in descriptive. Research findings total is 37.5 percent student able to use terminology, mathematics notation in view of relationship within model and situation even organize a question story. Then, total 62.5 percent student able to express mathematic ideas in oral and written and demonstrating for viewing at visual total 40 percent and 22.5 percent student able to understand, interpretation and good evaluation mathematic idea within oral and written, even though in visual, percentage ability mathematic communication is 40.6 percent with Low category.